Computer Aided Measurement System of Electrical Parameters of Pulsed Microplasma Processes in Electrolytic Solutions; 7 International conference on modification of materials with particle beams and plasma flows - Mamaev A. I.; Borikov V. N. Valery Nikolaevich; Mamaeva V. A.; Dorofeeva T. I. (Diagnostics of modified materials, 2004)
Title from the title-page.